Background to fib Model Code 2010 shear provisions – part II: punching shear. (2nd September 2013) - Muttoni, Aurelio; Ruiz, Miguel Fernández; Bentz, Evan; Foster, Stephen; Sigrist, Viktor
Abstract: This paper outlines the theoretical background to the punching shear provisions implemented in the fib Model Code for Concrete Structures 2010 and presents a practical example of their application. The aim is to explain the mechanical model that forms the basis for the punching design equations, to justify the relevance of the provisions and to show their suitability for the design and assessment of structures.